2012
DOI: 10.1097/mpg.0b013e31825048eb
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Diagnosis of Pediatric Acute Gastrointestinal Graft‐Versus‐Host Disease

Abstract: Rectosigmoid and combined upper endoscopic biopsies are equally sensitive for the diagnosis of acute GI GVHD in children. Flexible sigmoidoscopy can be done unsedated in appropriate patients at the bedside without anesthesia; it can be performed first to identify GI GVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 18 publications
6
30
3
Order By: Relevance
“…Several authors argue that endoscopic evaluation of the terminal ileum is not necessarily important for diagnosing acute GI‐GVHD because their studies showed that rectosigmoid biopsy diagnosed GI‐GVHD with high sensitivity. However, the terminal ileum was not well evaluated in previous studies . In our study, we showed that the diagnostic features in the colon were found more frequently on the left side of the colon of patients with acute GI‐GVHD, similar to previous reports .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several authors argue that endoscopic evaluation of the terminal ileum is not necessarily important for diagnosing acute GI‐GVHD because their studies showed that rectosigmoid biopsy diagnosed GI‐GVHD with high sensitivity. However, the terminal ileum was not well evaluated in previous studies . In our study, we showed that the diagnostic features in the colon were found more frequently on the left side of the colon of patients with acute GI‐GVHD, similar to previous reports .…”
Section: Discussionsupporting
confidence: 90%
“…One was the study of Sultan et al. who assessed the frequencies of positive endoscopic findings in 40 children (<18 years of age) with GI‐GVHD and eight children who were classified as non‐GVHD . The most common endoscopic findings in the pediatric patients with GI‐GVHD were normal mucosa in the stomach, duodenum, and rectosigmoid colon, but significant findings between the two groups were not detected.…”
Section: Discussionmentioning
confidence: 99%
“…However, these are older reports in which the final diagnosis was made later in the disease process [20]. By contrast, recent reports showed no relationships between mucosal injury severity and the diagnostic rate of pathological GI-GVHD [12,13,22]. These reports may support our present findings of no clear association between endoscopic mucosal injuries and GVHD manifestations.…”
Section: Discussioncontrasting
confidence: 80%
“…46 Both procedures can be performed simultaneously or in some instances in isolation if the GI symptoms suggest a localized process (diarrhea vs. nausea and vomiting). 46 Both procedures can be performed simultaneously or in some instances in isolation if the GI symptoms suggest a localized process (diarrhea vs. nausea and vomiting).…”
Section: Clinical Presentation and Endoscopic Findingsmentioning
confidence: 99%